INFLUENCE OF STRATEGIC PLANNING, LEADERSHIP EFFECTIVENESS, AND ENTREPRENEURIAL NETWORKING ON BUSINESS SUCCESS - Jayanto, Imam; Tresna, Indra Cahya; Sartika, Dewi; Purwoko, Bambang (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study investigates the influence of strategic planning, leadership effectiveness, and entrepreneurial networking on business success in small and medium enterprises (SMEs). Using a quantitative approach, data were collected from 250 SME managers and analyzed through reliability tests, correlation analysis, multiple regression, and structural equation modeling. The findings reveal that all three factors significantly and positively affect business success, with leadership effectiveness having the strongest impact, followed by strategic planning and entrepreneurial networking. These results highlight the critical role of effective leadership in driving organizational performance, while strategic planning and networking provide essential support in navigating dynamic market environments. The study offers valuable theoretical and practical implications, suggesting that SMEs should integrate strong leadership development, strategic planning, and networking activities to achieve sustainable growth and competitive advantage.